Penerapan Manajemen Waktu Melalui Jadwal Harian untuk Siswa Kelas 6 SD N 1 Ki Moyoso Boyolali - Intan Ayu Saputri; Galih Fajar Fadillah; Ernawati Ernawati; Syafawi Ahmad Qadzafi; Irfan Seno Aji (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Effective time management is an important skill for children to achieve their learning goals and daily activities. This study aims to implement time management through the use of a daily schedule specifically designed for children. The methods used in this activity include the presentation of materials related to time management, training in making a daily schedule, and short interviews with participants to evaluate the impact of the activity. This activity was carried out in a participatory manner with a fun approach and appropriate to the age of the participants. The results of the interviews showed that children felt more organized and were able to manage their daily activities better after participating in this program. In addition, they also reported improvements in focus, discipline, and productivity. Parents also observed positive changes in children's daily habits. This activity is expected to be the first step in educating children about the importance of good time management and forming positive habits that will be useful in their future lives.